2022
DOI: 10.3390/molecules27196148
|View full text |Cite
|
Sign up to set email alerts
|

Chrysomycin A Inhibits the Proliferation, Migration and Invasion of U251 and U87-MG Glioblastoma Cells to Exert Its Anti-Cancer Effects

Abstract: Chrysomycin A (Chr-A), an antibiotic from Streptomyces, is reported to have anti-tumor and anti-tuberculous activities, but its anti-glioblastoma activity and possible mechanism are not clear. Therefore, the current study was to investigate the mechanism of Chr-A against glioblastoma using U251 and U87-MG human cells. CCK8 assays, EdU-DNA synthesis assays and LDH assays were carried out to detect cell viability, proliferation and cytotoxicity of U251 and U87-MG cells, respectively. Transwell assays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In our study, remarkable downregulation of p-Akt and p-GSK-3β in Chr-A group was observed with Chr-A treatment, and their downstream, slug and MMP2, were also showed a significant decrease. Taken our previous work in vitro [14] together, Chr-A may function against glioblastoma via apoptosis regulation by Akt/GSK -3β signaling pathway confirming the KEGG enrichment analysis above.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our study, remarkable downregulation of p-Akt and p-GSK-3β in Chr-A group was observed with Chr-A treatment, and their downstream, slug and MMP2, were also showed a significant decrease. Taken our previous work in vitro [14] together, Chr-A may function against glioblastoma via apoptosis regulation by Akt/GSK -3β signaling pathway confirming the KEGG enrichment analysis above.…”
Section: Discussionsupporting
confidence: 81%
“…Chr-A has a group of benzonaphthopyranone glycosides, suggested to possess antitumor activity [8]. And it did show inhibitory effect to human U251 and U87-MG glioblastoma cells in vitro [14]. In the current study, we verified the antitumor activity of Chr-A in vivo using human U87-MG cells xenograft glioblastoma model, from which we found that intraperitoneal administration of both 3 and 10 mg/kg Chr-A suppressed the tumorigenicity.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…IRD-009 HCT-116 cells (colorectal cancer) Cell cycle modulator (G 0 /G 1 phase arrest), induction of apoptosis via DNA double strand interaction and damage [ 92 ] Prodigiosin Tripyrrole Pigment Serratia marcescens MDA-MB-231 cells and xenograft (breast cancer), MDA-MB-468 cells (breast cancer) Induction of apoptosis and downregulation of HSP90α. Suppression of migration and invasion and induction of apoptosis and via inhibition of Wnt/ β-catenin signaling [ 93 , 94 ] Pyocin S2 Bacteriocin Pseudomonas aeruginosa HepG2 cells (hepatocellular carcinoma), IM-9 cells (B-lymphoblastoid cell line) Induction of cell death [ 95 ] Pyocyanin Phenazine Pigment Pseudomonas aeruginosa MCF7 cells (breast cancer) Induction of apoptosis and necrosis [ 96 ] Rebeccamycin/NSC 655649 Indocarbozole Lechevalieria aerocoloigenes, Saccharothrix aerocolonigenes P388 cells (leukemia), L1210 cells (leukemia), B16 tumor model (melanoma), A549 xenograft (lung adenocarcinoma), Intercalates with DNA, promotes double strand breakage, inhibits topoisomerase I [ 97 , 98 ] Resistomycin Pentacyclic Polyketide Antibiotic Streptomyces aurantiacus AAA5 HepG2 cells (hepatocellular carcinoma), HeLa cells (cervical cancer), MDA-MB-231 xenograft (breast cancer), patient derived xenograft (breast cancer) Induction of cell death. Suppression of tumor progression, metastasis, and invasion by Pellino-1 inhibition and SNAIL/SLUG degradation [ 99 , 100 ] Salinomycin Carboxylic Polyether Ionophore Streptomyces albus OVCAR-8 (ovarian cancer), mammary cancer stem cells, patient -derived CLL cells Induction of apoptosis and G1 cell cycle arrest via Skp2 destabilization and Stat...…”
Section: Emerging Anticancer Agents From Microbial Metabolitesmentioning
confidence: 99%
“…1A) (19). ChryA belongs to the gilvocarcin family of C-aryl glycoside natural products (20) and shows various biological activities, including antibacteriophage (19), antibacterial (21)(22)(23)(24), antitumor (25,26), and antineuroinflammatory activities (27), implying its considerable potential as a multiple-target agent. Analogous compounds of ChryA, such as gilvocarcins, ravidomycins, and polycarcins, are also known as antibacterial and antitumor chemicals (21,28).…”
Section: Introductionmentioning
confidence: 99%